The Effect of Rosmarinus officinalis L Extract on the Inhibition of High Glucose-Induced Neurotoxicity in PC12 Cells: an In Vitro Model of Diabetic Neuropathy - Marzieh Rashidipour; Zahra Hajializadeh; Saeed Esmaeili-Mahani; Ayat Kaeidi * (Lorestan University of Medical Sciences, 2017)
Background and Aim: Diabetes mellitus and continued hyperglycemic condition prompt serious diabetic complications such as diabetic neuropathy. Numerous studies have shown the involvement of oxidative stress and high glucose-induced cell death in the progress of diabetic neuropathy. Rosmarinus officinalis L has been suggested in the literature as an anti-diabetic herbal medicine that contains potent antioxidant components. Therefore, the neuroprotective effect of Rosmarinus officinalis L (RE) extract was investigated in glucose-induced neurotoxicity via pheochromocytoma )PC12( cells as an appropriate in vitro model of diabetic neuropathy. Materials and Methods: Cell viability was determined using MTT assay. Cleave caspase-3 and Bax: Bcl2 ratio, as biochemical parameters of cellular apoptosis, were measured by western blotting analysis. Results: Our data showed that a 4-fold elevation in the medium glucose significantly reduced cell viability (P < 0.01) and increased caspase-3 activation (P < 0.01) as well as Bax: Bcl2 ratio (P < 0.05) in PC12 cells after 24 h. Incubation of high glucose medium cells with 60μg/ml RE extract decreased high glucose-induced cell toxicity and prevented caspase-3 activation and Bax: Bcl2 ratio. Conclusion: It could be concluded that RE extract is effective in the protection against hyperglycemia-induced cellular toxicity. This could be relevant to the prevention of apoptosis. Moreover, the results suggest that RE has the therapeutic potential to attenuate diabetes complications such as that neuropathy.